FOOD OF SMALL-SIZED OIL SARDINE OF THE MANGALORE AREA - Dhulkhed, M H (Indian Journal of Fisheries, 2011)
The food of oil sardine ranging 40-79 mm in length consisted of diatoms, dinoflagellates and copepods. There seems to be no consistency in regard to various food items in different size groups. Studies have also shown the absence of selective feeding in small oil sardine.